Strength behavior and microstructural characteristics of tropical laterite soil treated with sodium silicate-based liquid stabilizer - Latifi, Nima (Springer, 2014)
Although the effects of nontraditional stabilizers on the geotechnical properties of tropical soils has been the issue of investigation in recent years, the micro-structural characteristics of nontraditional soil additives and in particular selected additive (TX-85) have not been fully studied. Nontraditional soil stabilization additives are widely used for stabilizing marginal materials. These additives are low-cost alternatives to traditional construction materials and have different compositions. They also differ from one another while interacting with soil. In line with that, it was the objective of this research to investigate the strength properties and physicochemical mechanisms related to tropical laterite soil mixed with the liquid stabilizer TX-85. Macro-structure study, i.e., compaction, and unconfined compression strength test were used to assess the engineering and shear properties of the stabilized laterite soil. In addition, the possible mechanisms that contributed to the stabilization process were discussed using various spectroscopic and microscopic techniques such as X-ray diffractometry (XRD), energy-dispersive X-ray spectrometry, scanning electron microscopy, and Fourier transform infrared spectroscopy. From engineering point of view, the results indicated that the strength of TX-85 stabilized laterite soil improved significantly. The degree of improvement was approximately four times stronger than natural soil after a 7-day curing period. The XRD showed no crystalline products (gel form). Moreover, weathering effects were obvious in TX-85 treated samples in most of clay minerals' peak intensities. These effects were reduced especially for kaolinite mineral inside the soil with curing time.